The new system of the talent development program in Hungarian soccer - Csáki István; Géczi Gábor; Kassay Lilli; Déri Diana; Révész László; Dávid Zalai; Bognár József (Sciendo, 2014)
Study aim: due to a series of failures and the drastic reduction in the quality of Hungarian soccer, greater emphasis should be put on coaches' professional development and talent development programs. The aim of this study was to present the newly established Hungarian Soccer Development Program that focuses on the development of youth talent.